NICHE MARKET IN FANGIRLING PHENOMENON - Swandewi, Ni Kadek; Citrawati, Luh Putu; Asmarani, I.G.A. Ratih (Program Studi Akuntansi IKOPIN, 2023)
Specific segmentation in managing the target audience in events can take advantage of phenomena or trends that are currently happening in society. One of the current familiar phenomena to millennials and gen Z is the phenomenon of